2014
DOI: 10.3171/2014.6.jns131433
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression profiling elucidates molecular signaling networks that can be therapeutically targeted in vestibular schwannoma

Abstract: ObjectVestibular schwannomas (VS) are common benign tumors of the vestibular nerve that cause significant morbidity. The current treatment strategies for VS include surgery or radiation, with each treatment option having associated complications and side effects. The transcriptional landscape of schwannoma remains largely unknown.MethodsIn this study the authors performed gene-expression profiling of 49 schwannomas and 7 normal control vestibular nerves to identify tumor-specific gene-expression patterns. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…One of these pathways, insulin receptor signaling, has been implicated in VS tumorigenesis. 2,5 Our results imply that this pathway may be more important in VSs lacking mutational hits in the NF2 gene.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…One of these pathways, insulin receptor signaling, has been implicated in VS tumorigenesis. 2,5 Our results imply that this pathway may be more important in VSs lacking mutational hits in the NF2 gene.…”
Section: Discussionmentioning
confidence: 69%
“…In recent years, several transcriptome studies using microarray techniques have also added to the understanding of this disease. 1,2,11,61,66 6,19,24,65 The predominant view regarding sVS pathobiology is that loss of function of merlin, encoded by the NF2 gene, is the main driver of tumorigenesis. However, controversies exist because several reports indicate that a proportion of tumors have an intact NF2 gene and normal mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inactivation of the NF2 gene is not found in every VS, which possibly indicates additional mechanisms that might be involved in tumorigenesis [3,32]. Gene expression profiling and pathway analysis in other studies have identified a high range of tumor-related candidate genes and pathways that contribute to the biology of VS [19,26,[33][34][35][36][37][38][39]. None of these studies, however, have investigated differences between irradiated tumors and their controls.…”
Section: Introductionmentioning
confidence: 99%
“…Gelareh zaDeh, M.D., Ph.D., 7 saMeer aGnihotri, Ph.D., 1 isabel GuGel, M.D., 2 Marc reMke, M.D., 1,3,4 antje borneMann, M.D., Ph.D., 5 GeorGios Pantazis, M.D., 6 stePhen c. We are grateful to Drs. Peruzzi and Lonser for their positive review of our work and for highlighting some of the key points arising from the results we obtained in our study.…”
Section: Responsementioning
confidence: 99%
“…Agnihotri and colleagues analyzed the differential gene expression between vestibular schwannomas (VSs) and normal control vestibular nerve tissue. 1 They uncovered a rather striking pattern of gene dysregulation in VSs. More than 1400 and 2800 genes were downregulated or upregulated, respectively, in VSs compared to vestibular nerves.…”
mentioning
confidence: 99%